2021
DOI: 10.3390/f12111524
|View full text |Cite
|
Sign up to set email alerts
|

Social Preferences of Young Adults Regarding Urban Forest Recreation Management in Warsaw, Poland

Abstract: The paper presents results of questionnaire research conducted to determine social preferences regarding leisure in Warsaw municipal forests (WMF) (Poland). The preferences pertained to frequency of visits and willingness to pay for recreational infrastructure in a forest depending on its appearance, level of development, and the respondent’s income. The data were processed using statistical analysis (ANOVA Friedman test, U Mann–Whitney test, logistic regression). The results show that the higher the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In manor parks, the level of income influences the awareness of their historical value and the presence of additional tourist attractions in their area. In comparison, in forests in the Warsaw area, it was found that people with a higher income were more likely to visit natural forest areas (e.g., a strict nature reserve or a commercial forest without recreational infrastructure with recreational opportunities such as walking along paths and picking mushrooms and berries) [34]. At the same site, no such relationship was found for forests with refined recreational infrastructures.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In manor parks, the level of income influences the awareness of their historical value and the presence of additional tourist attractions in their area. In comparison, in forests in the Warsaw area, it was found that people with a higher income were more likely to visit natural forest areas (e.g., a strict nature reserve or a commercial forest without recreational infrastructure with recreational opportunities such as walking along paths and picking mushrooms and berries) [34]. At the same site, no such relationship was found for forests with refined recreational infrastructures.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, they are open to the general public, and accessing them in Poland is usually free. Forests, due to their high level of biodiversity and their numerous ecological, social, protective and economic functions, should be subject to a comprehensive assessment for all the services they provide [33,34]. The authors of studies on manor parks have highlighted the significant role of manor parks in terms of ecological [35][36][37], social and landscape value [15], and there is also a considerable number of publications emphasizing the historical aspect of these sites [13,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing human development and concentration of population in the urban areas is closely related to the quality of citizens´ lives, safe and clean environment, and adaptation to extreme climate conditions in the cities. During the 20 th -century strategies related to greenways, ecological design, sustainable development of cities have been elaborated (Supuka, 2008;Mandziuk et al, 2021a). Sustainable shaping of green areas in cities is supported by scientifi c research, connected with the current policy of the European Union and supported by the local governments and residents of cities.…”
Section: Introductionmentioning
confidence: 99%